Group influence activities and the performance of strategic initiatives - Lechner, Christoph; Floyd, Steven W. (Strategic Management Journal, 2012)
This study examines relationships between group influence activities and the performance of strategic initiatives. Theory suggests that the strength of these relationships is contingent upon the degree of exploration inherent in an initiative's goals. An analysis of 96 initiatives in three large firms supports the moderating role of exploration for the use of formal authority and coalition building, demonstrating that these group influence activities are more important to performance in more exploratory initiatives. Although the direct relationship between rational justification and initiative performance is significant, there is no evidence of the moderating effect for this form of influence. The results show how groups associated with strategic initiatives use different forms of influence to reduce the investment and political uncertainties that limit initiative performance. Copyright © 2011 John Wiley & Sons, Ltd.